While This is Difficult for an Adult, A Child Can Handle It Easily - F. Todd Goodson (Educational Considerations, 2023)
I attempted to learn to play chess when my daughter was in middle school. At that time, she joined an after-school chess club sponsored by a teacher she admired, and I felt obligated to follow her into the game. She assumed the role of teacher, and she instructed me in the game. Eventually, my daughter moved on to a point where she no longer required my services as her student, and I made a conscious decision not to invest more time in chess. I either wanted to be good, or I didn’t want to continue, and I knew becoming good would take more time than I felt being good at chess was worth. In this issue of Educational Considerations, we have a provocative piece from a European scholar Gulcin Karakus, who offers a comprehensive review of the impact of chess on student learning--and who has caused me to reconsider chess.
Keywords: Chess; student learning; exploratory learning